PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) DAN MEDIA BENDA KONKRET DALAM PENINGKATAN PEMBELAJARAN IPA SISWA KELAS III SDN 3 PANJER - Puspitawarti, Dien (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Applying of CTL and Concrete Object media in Improving of Natural Science Learning in III SDN 3 Panjer. The aims of this research is discribing applying of CTL and Concrete Object media in Natural Science learning and improve Science Learning in III grade of Elementary School. Subject of this research is a students in III grade by consist of 26 students. This research is a Collaborative Classroom Action Research. Procedure research are planning, action, observation, and reflection. This research in two cycle, each cycle three meeting. The result of research indicate that applying of CTL and Concrete Object media can improve Natural Science Learning in III grade Elementary School. Keyword: CTL, Concrete Object media, Natural Science learning. Abstrak: Penerapan Model Contextual Teachinag and Learning (CTL) dan Media Benda Konkret dalam Peningkatan Pembelajaran IPA pada Siswa Kelas III SD Negeri 3 Panjer. Tujuan penelitian ini adalah mendeskripsikan penerapan model CTL dan Media Benda Konkret dalam pembelajaran IPA dan meningkatkan pembelajaran IPA pada kelas III Sekolah Dasar. Subjek penelitian ini adalah siswa kelas III berjumlah 26 siswa. Penelitian ini menggunakan teknik Penelitian Tindakan Kelas kolaboratif. Prosedur penelitian tindakan kelas berupa perencanaan, pelaksanaan, observasi dan refleksi. Pelaksanaan tindakan dilaksanakan dalam dua siklus masing-masing siklus tiga pertemuan. Hasilnya menunjukkan bahwa penerapan model CTL dan Media Benda Konkret dapat meningkatkan pembelajaran IPA pada siswa kelas III Sekolah Dasar. Kata Kunci: model CTL, Benda Konkret, IPA.